The Ruby key - Lisle, Holly (New York : Scholastic, 2008)
In a world where an uneasy peace binds Humans and Nightlings, fourteen-year-old Genna and her twelve-year-old brother Dan learn of their uncle's plot to gain immortality in exchange for human lives, and the two strike their own bargain with the Nightling lord, which sets them on a dangerous journey along the Moonroads in search of a key.
Keywords: Adventure -- Fiction; Sun and moon -- Fiction